MicroRNAs and cancer resistance: A new molecular plot. Issue 5 (17th March 2016) - Fanini, F; Fabbri, M
Abstract : The most common cause of cancer relapse is drug resistance, acquired or intrinsic, which strongly limits the efficacy of both conventional and new targeted chemotherapy. MicroRNAs (miRNAs) are a growing, large family of short noncoding RNAs frequently dysregulated in malignancies. Although the mechanism of miRNA‐mediated drug resistance is not fully understood, an increasing amount of evidence suggests their involvement in the acquisition of tumor cell drug resistance, pointing towards the need for novel and more innovative therapeutic approaches. Use of antagomiRs or mimics can modulate specific miRNAs in order to restore gene networks and signaling pathways, perhaps optimizing chemotherapies by increasing cancer cell sensitivity to drugs. The aim of this review is to provide a state‐of‐the‐art scenario with regard to the most recent discoveries in the field of miRNAs involved in the process of resistance to cancer therapy.